Pemberdayaan Masyarakat Berbasis Potensi Lokal Melalui EPOLIK Di Ngesong Sedayulawas Brondong Lamongan - rohmah, nafilatur (Journal of Community Dedication and Development (Pengabdian Kepada Masyarakat), 2022)
Objective. Local potentional-based Creative industry is a method to improve society's prosperity. Society's bewilderment in processing natural products into creative industries is one of the reasons why people sale off their harvests that results low-price raw products. Women (in this case housewives) in Ngesong village required an education or training regarding local potential-based creative industries. This society's empowerment discussed about enhancement of society's prosperousness with a program called EPOLIK (Edukasi Pemanfaatan Potensi Lokal sebagai Industri Kreatif). It is an educational Program on the use of local potentials as creative industries. The program was formulated for housewives in Ngesong village. Materials and Methods. The empowerment in this research used PAR (Participatory Action Research) method, which was a collaboration between researchers and the Ngesong people. The collaboration included: formulating the issues/problems, Planning the actions, executing the actions and evaluating the outcomes. Results. The results of the empowerment are: (1) the assisted participants can make processed Sapodilla ingredients into cakes and drinks called Maneela Cake and Maneela Syrup: (2) awareness within themselves, namely: (a) awareness that there is potential in their area that should be developed; (b) Awareness that the developed local potential can have economic value; (c) Delicacy in that selling goods directly with goods processed into semi-finished goods has more selling value; (d) growing creative industries starting from home. Conclusion. This empowerment activity through EPOLIK provides experience for assisted subject housewife to find potential natural resources that can be processeed into value-added products to increase economic welfare. This activity also provides skills to assisted subject husewife in processing local potential in the form of Sapodilla fruit into Maneela cake and Maneela Syrup. In addition, this activity can increase the motivation of assisted subject mothers as creative industry players by utilizing local potential to improve welfare.